A case report: Comorbidity of Rhinocerebral mucormycosis and pulmonary aspergillosis with challenging diagnosis - Wang, Qi; Huang, YangYiYi; Ma, HaiNa; Fan, Guo-Kang (Frontiers in Medicine, 2024)
Background: Mucormycosis is a rare opportunistic invasive fungal disease. Rhinocerebral mucormycosis (RCM) is clinically difficult to diagnose, and patients often die due to delayed diagnosis.Case description: A patient with concurrent pulmonary aspergillosis was diagnosed with RCM caused by Rhizopus through metagenomic Next-Generation Sequencing (mNGS). Despite comprehensive treatment including surgery, amphotericin B, and posaconazole, the patient tragically passed away. The treatment was delayed due to repeated cultures of secretions were negative and pathological examination could not clarify which fungus is infected.The clinical manifestations of RCM are not specific in the early stage, but the infection progresses rapidly. Therefore, early and accurate diagnosis is very important. mNGS is helpful for patients suspected of RCM, especially when conventional microbiology tests were negative.